Realizing high ceramic yield and low shrinkage of in-situ formed lightweight 3D-SiC(rGO)px polymer-derived ceramics with excellent fracture toughness. Issue 17 (1st December 2020) - Zhuang, Kun; Lin, Shuyu; Huang, Wenyan; Liao, Liang; Zheng, Yinong; Li, Lingjie; Ning, Zhonghao; Jin, Chao; Lan, Siqi; Zhang, Yinggan; Yao, Rongqian
Abstract: Integration of high ceramic yield, low shrinkage and excellent fracture toughness in polymer-derived ceramics (PDCs) is challenging. Highly cross-linked polycarbosilane-vinyltriethoxysilane-graphene oxide (PCS-VTES-GO, PVG) precursors spontaneously interact with dense high-strength SiC(rGO)p fillers for abundant Si-dangling bonds at their interfaces. Herein, an ingenious strategy via re-pyrolysis process of ball-milling-induced SiC(rGO)p /PVG blends is proposed to fabricate 3D-SiC(rGO)p x PDCs. The in-situ formed innovative three-dimensional (3D) honeycomb cellular net-like structure, with dense β-SiC(SiO2 )/SiO x C y /Cfree (rGO) framework providing high strength while tiny micro-sized pores relaxing stress at the tip, effectively improves molding process, ceramic yield and mechanical properties of PDCs. Particularly, lightweight 3D-SiC(rGO)p0.6 PDCs display dense surface, satisfactory hardness (3.96 GPa) and excellent fracture toughness (3.21 MPa m 1/2 ), especially high ceramic yield (94.49%) and low linear shrinkage (5.00%), realizing outstanding values ever reported for PDCs to the best of our knowledge. During re-pyrolysis process, they have struck perfect balance and achieved a combination of equal volume of inwardly shrinking PVG precursors and outwardly expanding SiC(rGO)p fillers. For the first time, such synergistic effects of flexible PVG with rigid SiC(rGO)p in this way pave a practical route toward reliable mass-produced 3D-SiC(rGO)p x PDCs with potential applications in emerging aerospace propulsion components. Graphical abstract: Image 1 Highlights: Dense/lightweight 3D-SiC(rGO)p x PDCs were ingeniously obtained for the first time. The ceramic yield reaches 94.49%, which is the highest value ever reported for PDCs. Sufficiently low shrinkage decreased to 5.00% is conducive to complex shape accuracy. In-situ formed 3D net-like structure (bionic structure of dentin) owns high strength. Synergistic effect of flexible PVG with rigid SiC(rGO)p is creatively proposed.